The Broncho Rider Boys on the Wyoming Trail : Or, A Mystery of the Prairie Stampede - Fowler, Frank (Salt Lake City, UT : Project Gutenberg, 2012)
"The Broncho Rider Boys on the Wyoming Trail" by Frank Fowler is an adventure novel written in the early 20th century. The story revolves around three young riders$1 (BAdrian Sherwood, Donald Mackay, and Billie Winkle$1 (Bwho are journeying from the Arizona border into the Wyoming cattle country. As they make their way along the trail, they encounter challenges and unexpected adventures that highlight their camaraderie and resourcefulness, notably dealing with the trials of bronco riding and the thrill of the Wild West. The opening of the book introduces the trio as they conclude a lengthy ride across the rugged terrain, preparing to reach the Bar-S Ranch. During their travels, they demonstrate their unique personalities, including Billie's struggles with his weight and his stubbornness to master bronco riding. The narrative sets the stage for their adventures as they camp, dine, and joke together, hinting at the coming excitement when they find themselves untangling a series of mysterious events involving cattle rustlers. This opening portion effectively establishes the characters' relationships, the challenges they face, and foreshadows the thrilling escapades awaiting them on the Wyoming trail. (This is an automatically generated summary.)s
Release date is 2012-04-30
E-text prepared by Roger Frank and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the HathiTrust Digital Library (http://www.hathitrust.org/digital_library)
Keywords: Ranches -- Juvenile fiction; Cowboys -- Juvenile fiction; Wyoming -- Juvenile fiction